Antibacterial activity of nanoporous gold against Escherichia coli and Staphylococcus epidermidis. Issue 9 (16th May 2017) - Hakamada, Masataka; Taniguchi, Seiji; Mabuchi, Mamoru
Abstract: Abstract : Conventional metallic antibacterial materials release metal ions and reactive oxygen species (ROS) for killing bacteria. Herein, we found that nanoporous gold (NPG) exhibits antibacterial activity (AA) at an intermediate relative humidity (RH) of 60% against Escherichia coli and Staphylococcus epidermidis in contrast to the inert behavior of bulk gold. The dependence of AA on RH, morphological observations of bacteria on NPG, and transcriptomic analyses of NPG-treated Escherichia coli were investigated. These observations collectively suggest that biological processes in cell walls containing peptidoglycan and cell membranes are significantly disrupted by direct contact with NPG. Metal ions and ROS were not detected, and therefore are not responsible for the present antibacterial properties of NPG. The catalytic nature of NPG may be responsible for its AA, probably because of lattice distortion at the surface of nanosized ligaments with large curvature.